The Correlation between Lipoprotein-Associated Phospholipase A2 and Atherosclerosis (ox-LDL) in Centrally Obese Men - Priscilla Dian Ari; Ellis Susanti; Ilhamjaya Patellongi (The Indonesian Biomedical Journal, 2012)
BACKGROUND: Obesity is closely associated with atherosclerosis. Obesity and atherosclerosis are closely associated with inflammatory disease. Atherosclerosis constitutes a multifactorial disorder affecting the arterial wall, which is initiated by dyslipidemia and excerbated by inflammation. Plasma levels of lipoprotein-associated phospholipase A2 (Lp-PLA2) and oxidized low density lipoprotein (ox-LDL) have been identified as risk factors for cardiovascular disease.  Lp-PLA2 is the sole enzyme responsible for the hydrolysis of oxidized phospholipids (oxPL) on LDL particles in atherosclerosis plaque. Plasma level of oxLDL is associated with inflammation and plays an important role in the development of atherosclerosis. The aim of this study was to assess the correlation between Lp-PLA2 and atherosclerosis (oxLDL) in centrally obese men.METHODS: This was a cross-sectional study involving 71 men with central obesity with waist circumference >90 cm, aged 30-60 years old. Lp-PLA2 measurement was done by sandwich enzyme immunoassay. oxLDL measurement was done by ELISA method. RESULTS: Results of this study showed that central obesity correlated positively with oxLDL (r=0.258; p=0.040) and Lp-PLA2 >422 ng/mL correlated positively with oxLDL (r=0.331; p=0.042).CONCLUSIONS: We conclude that there is a correlation of Lp-PLA2 with atherosclerosis (oxLDL) in men with central obesity.KEYWORDS: obesity, Lp-PLA2, oxLDL, atherosclerosis